Über die Hindernisse der Schnittflächen in zweimaliger Faserung - Matuzevičius, A. (Lithuanian Mathematical Journal, 1961)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Матузявичюс. Препятствия для секущих поверхностей двукратных расслоений A. Matuzevičius. Kertamųjų paviršių kliūtys dvigubuose sluoksniavimuose